Functional Characterization of an Aspergillus fumigatus Calcium Transporter (PmcA) that Is Essential for Fungal Infection - Dinamarco, Taisa Magnani; Freitas, Fernanda Zanolli [UNESP]; Almeida, Ricardo S.; Brown, Neil Andrew; dos Reis, Thaila Fernanda; Zambelli Ramalho, Leandra Naira; Savoldi, Marcela; Goldman, Maria Helena S.; Bertolini, Maria Celia [UNESP]; Goldman, Gustavo Henrique (Public Library Science, 2012)
Aspergillus fumigatus is a primary and opportunistic pathogen, as well as a major allergen, of mammals. The Ca+2-calcineurin pathway affects virulence, morphogenesis and antifungal drug action in A. fumigatus. Here, we investigated three components of the A. fumigatus Ca+2-calcineurin pathway, pmcA,-B, and -C, which encode calcium transporters. We demonstrated that CrzA can directly control the mRNA accumulation of the pmcA-C genes by binding to their promoter regions. CrzA-binding experiments suggested that the 5'-CACAGCCAC-3' and 5'-CCCTGCCCC-3' sequences upstream of pmcA and pmcC genes, respectively, are possible calcineurin-dependent response elements (CDREs)-like consensus motifs. Null mutants were constructed for pmcA and -beta and a conditional mutant for pmcC demonstrating pmcC is an essential gene. The Delta pmcA and Delta pmcB mutants were more sensitive to calcium and resistant to manganese and cyclosporin was able to modulate the sensitivity or resistance of these mutants to these salts, supporting the interaction between calcineurin and the function of these transporters. The pmcA-C genes have decreased mRNA abundance into the alveoli in the Delta calA and Delta crzA mutant strains. However, only the A. fumigatus Delta pmcA was avirulent in the murine model of invasive pulmonary aspergillosis.